PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN ARTICULATE STORYLINE 3 PADA TEMA 8 LINGKUNGAN SAHABAT KITA - Suci Lestari; R. Teti Rostikawati; Resyi Abdul Gani Abdul Gani (STKIP Subang, 2023)
Development of Interactive Learning Media Using Articulate Storyline 3 on Theme 8 The Environment of Our Friends. This study aims to develop and determine the feasibility of interactive learning media Articulate Storyline 3 theme of the environment of our friends subtheme of humans and the learning environment 2. This study uses the type of Research and Development (R&D) studies, these research and development steps use the ADDIE model with 5 stages consisting of Analysis, Design, Development, Implementation and Evaluation stages. This research was implemented at SDN Bantarkemang 1 with class V as the research subject. The data collection techniques used were interviews, observations, questionnaires, and documentation. The feasibility of the media products developed obtained a percentage of 83% media experts, 100% language experts, and 94% material experts with very feasible criteria. While the students response was 96,64%, the user response (teacher) was 97,77%, and the N-Gain score obtained was 0,56 with a moderate category, which means that the media products developed are effective enough to be used in learning. Based on the results of the study, it can be concluded that the interactive learning media Articulate Storyline 3 developed in the study proved feasible and effective enough to be used during learning.